DEVELOP APPSEPTION THROUGH SCENE SETTING WITHIN LEARNING MATH - Astri Setyawati (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2019)
Mathematics is a subject that is considered boring. This assumption needs to be changed, therefore it is necessary to make changes in mathematics learning. Interesting learning can begin with activities that attract the attention of students. Interesting learning activities are expected to foster students' desire to learn mathematics. Therefore, early learning activities or apperception required an interesting strategy. Apperception aims to link the initial knowledge with the knowledge to be learned. Finding interesting strategic ideas to initiate learning activities and which can connect the initial knowledge possessed by students with the material to be studied is one of the difficulties that are felt by many mathematics teachers. In this study, the scene setting will be discussed as one of the strategies that can be applied to apperception activities in order to foster students' desire to learn mathematics. Scene setting is a strategy that is carried out by providing a learning experience before entering into the core material. The aim is to foster curiosity about the material to be studied. Some sources of scene setting ideas include: life safety, benefits, cause and effect, delivery of information or news, imaginative stories, and films. This study aims to describe the application of scene settings to develop apperception in learning mathematics.